A poison dark and drowning - Cluess, Jessica (Cluess, Jessica. Kingdom on fire, 2017)
Even though she is not the chosen one--the sorcerer destined to defeat all seven Ancient demons terrorizing humanity in Victorian England--Henrietta Howel battles alongside the sorcerers in the war against the demons, journeying to find mystical weapons, gather allies, and uncover secrets about herself and her enemies.